1999
DOI: 10.1063/1.370171
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of fields and charge carriers in cylindrical nanosize silicon-based metal–oxide–semiconductor structures

Abstract: Articles you may be interested inModeling the capacitance-voltage response of In 0.53 Ga 0.47 As metal-oxide-semiconductor structures: Charge quantization and nonparabolic corrections Appl. Phys. Lett. 96, 213514 (2010); 10.1063/1.3436645 Calculation of the direct tunneling current in a metal-oxide-semiconductor structure with one-side open boundary Modeling of charge quantization and wave function penetration effects in a metal-oxide-semiconductor system with ultrathin gate oxide J. Appl. Phys. 94, 5273 (2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…The study of the charge distribution in the cylindrical MOSFET with closed gate electrode in the state of the thermodynamical equilibrium (see Ref. 31 ) has shown that the concentration of holes is much lower than that of electrons, so that electron transport is found to provide the main contribution to the current flowing through the SOI MOSFET. For that reason, holes are neglected in the present transport calculations.…”
Section: The Hamiltonian Of the Systemmentioning
confidence: 99%
“…The study of the charge distribution in the cylindrical MOSFET with closed gate electrode in the state of the thermodynamical equilibrium (see Ref. 31 ) has shown that the concentration of holes is much lower than that of electrons, so that electron transport is found to provide the main contribution to the current flowing through the SOI MOSFET. For that reason, holes are neglected in the present transport calculations.…”
Section: The Hamiltonian Of the Systemmentioning
confidence: 99%
“…(4) of Jang and Liu 5 ] cannot be used for the cylindrical MOSFET. 9 We hereafter assume that the channel is fully depleted of majority carriers (holes), leading to Q im −πa 2 qN − A . The drain current I D (z) is proportional to Q mo (z) and the gradient of the electron quasi-Fermi potential V n (z):…”
mentioning
confidence: 99%
“…The main elements of such model are described in the next section. We refer to the original papers for more details [18,19].…”
mentioning
confidence: 99%
“…5 The quantum MOSFET model Calculations were performed in [18,19] for a cylindrical MOS structure, with the gate covering the cylinder mantle and the source/drain contacts at both ends (Fig. 3a).…”
mentioning
confidence: 99%
See 1 more Smart Citation